THE SUBSTANTIAL SIDES OF PURITY IN HONORE DE BALZAC’S INNOCENCE - Oktavia, Salsabila Adinda; Pasopati, Rommel Utungga; Kirana, Kheista Sasi; Pangestu, Imelza Novia Rakhmadani; Riza, Dwi Ainur (ELite Journal : International Journal of Education, Language and Literature, 2024)
This article explores the matter of purity in Honore de Balzac’s flash fiction entitled Innocence. Purity refers to the idea that certain actions or behaviors are considered morally pure or impure based on societal norms and values. Innocence is a Honore de Balzac’s flash fiction that talks about innocence or a high curiosity spirit possessed by children. Through qualitative method and explorative approach, it is analyzed through this flash fiction that innocence is the main symbol of purity. Little Francis and Margot are two little pure spirits who live. They try new things. They notice a portrait of two figures, which is actually an image of Adam and Eve. However, because the children's minds have not matured enough and they have not been exposed to more knowledge, they do not recognize which one is Adam and which is Eve, because the figure does not wear clothes, therefore Little Francis and Margot are unsure which is Adam and which is Eve. The purity of the children is a direct mirror of innocence, which is the essence of Balzac's flash fiction. Children will only know some things because they are still pure. Purity is a natural aspect that all children have. In conclusion, adult people will laugh at them, but the children are still pure since they reflect their childhood matters.